2012
DOI: 10.1021/jp300353y
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on a HS Sensing Reaction Utilizing a Pyrylium Derivative

Abstract: In this paper, we present a comprehensive computational study on the hydrogen sulfide sensing mechanism in aqueous solution using a pyrylium derivative. The possible sensing mechanisms were investigated under the neutral condition and acidic condition in the gas phase and in aqueous solution. The pyrylium–thiopyrylium transformation under the neutral condition is thermodynamically unfavorable, while it is greatly facilitated in the acidic condition catalyzed by a hydronium cation. In addition, the UV–vis absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…2,4,6‐Triphenylpyrylium salt ( TPP , Figure a), a heterocyclic system with unique photophysical properties, shows great potential for sensor applications . However, some inherent limitations of the TPP core scaffold, such as instability in water, short emission wavelength, and low quantum yields, hinder its application in biological imaging and probe development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,6‐Triphenylpyrylium salt ( TPP , Figure a), a heterocyclic system with unique photophysical properties, shows great potential for sensor applications . However, some inherent limitations of the TPP core scaffold, such as instability in water, short emission wavelength, and low quantum yields, hinder its application in biological imaging and probe development.…”
Section: Resultsmentioning
confidence: 99%
“…Design 2,4,6-Triphenylpyrylium salt (TPP,F igure 1a), ah eterocyclic system with unique photophysical properties, shows great po-tential for sensor applications. [38,[40][41][42] However,s ome inherent limitations of the TPP core scaffold, such as instability in water, short emission wavelength, and low quantum yields, hinder its application in biological imaging and probe development. Densityf unctional theory (DFT) calculations indicated that the p electrons in the LUMO of TPP are delocalized over the entire p-conjugated 2,4,6-triphenylpyrylium framework, whereas the HOMO is mostly localized on the 2,6-phenyl substituents (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The transition states have also been verified by pseudo-IRC (intrinsic reaction coordinate) calculations. 77,78 The 6-31G(d) basis set is a good compromise between efficiency and accuracy 64,79,80 and has been proven to reproduce well the molecular parameters. The further expansion of the basis set such as 6-311+G(d,p) has less impact on the accuracy of the molecular geometries and activation energy.…”
Section: Calculation Methods and The Model Compoundsmentioning
confidence: 99%
“…In our previous study, 64 the pyrylium−thiopyrylium transformation under acidic condition was modeled by involving one hydronium ion to the reaction coordinate; its activation energy was reported to be 40.2 kcal/mol. This high activation energy indicates that the pyrylium−thiopyrylium transformation involving only a hydronium ion is kinetically unfavorable.…”
Section: Introductionmentioning
confidence: 99%
“…1). For instance, for LN1 such transformation involves a red-shift of the absorption band from 540 nm for the pyrylium derivative to 580 nm for LN3 [28]. This is a highly selective reaction and only hydrogen sulfide and sulfide anions are able to induce such a color change from magenta to blue.…”
Section: Introductionmentioning
confidence: 99%